Scaffolding in indoor and outdoor mobility: a wearable and mobile application for senior tourism in a playable city - Costa, Liliana Vale (2021)
The growth of urban population and the challenges of an ageing society have brought to the fore the need of innovative ways to re-invent sustainable healthy ageing lifestyles and meet the growing demand on transport and residents’ assistance with ageing-in-place. Fatalities involving older adult pedestrians is a major problem in EU urban areas, given the general lack of information about traffic and road conditions. Indoor and Outdoor Mobility are also likely to affect Senior Tourism and older adults’ travel patterns. This paper proposes a digital application designed for wearables and mobile devices that engages the users in a set of missions and routes that are customized to their context and mobility condition, based on a multi-peer review system.